2021
DOI: 10.3168/jds.2020-19627
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of colostrum composition and fatty acid status in neonatal calves by maternal supplementation with essential fatty acids and conjugated linoleic acid starting in late lactation

Abstract: Sufficient maternal supply of essential fatty acids (EFA) to neonatal calves is critical for calf development. In the modern dairy cow, EFA supply has shifted from α-linolenic acid (ALA) to linoleic acid (LA) due to the replacement of pasture feeding by corn silagebased diets. As a consequence of reduced pasture feeding, conjugated linoleic acid (CLA) provision by rumen biohydrogenation was also reduced. The present study investigated the fatty acid (FA) status and performance of neonatal calves descended from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…During gestation and via the intake of colostrum and milk, the maternal supply of essential fatty acids (EFA) can be transferred to the calf [ 13 , 25 ]. The first results of the present study showed increased n-3 fatty acid and CLA concentrations, as well as a decreased n-6: n-3 fatty acid status in colostrum and in the blood plasma of calves when dams were supplemented with EFA (mainly n-3 fatty acids provided by linseed oil) and CLA ( cis -9, trans -11 CLA and trans -10, cis -12 CLA) during late gestation and early lactation [ 26 , 27 ]. Therefore, the present study aimed to investigate the inflammatory and oxidative status as well as anti-oxidative response of calves born from cows, supplemented abomasally with coconut oil as a saturated fatty acid source, EFA and CLA during late pregnancy and early lactation, within the first 5 days after birth.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…During gestation and via the intake of colostrum and milk, the maternal supply of essential fatty acids (EFA) can be transferred to the calf [ 13 , 25 ]. The first results of the present study showed increased n-3 fatty acid and CLA concentrations, as well as a decreased n-6: n-3 fatty acid status in colostrum and in the blood plasma of calves when dams were supplemented with EFA (mainly n-3 fatty acids provided by linseed oil) and CLA ( cis -9, trans -11 CLA and trans -10, cis -12 CLA) during late gestation and early lactation [ 26 , 27 ]. Therefore, the present study aimed to investigate the inflammatory and oxidative status as well as anti-oxidative response of calves born from cows, supplemented abomasally with coconut oil as a saturated fatty acid source, EFA and CLA during late pregnancy and early lactation, within the first 5 days after birth.…”
Section: Introductionmentioning
confidence: 89%
“…From day 3 onwards, calves were fed an amount of 12% of BW per day, which was provided in 2 meals. Details on feeding management including the milk composition were recently published in a companion paper [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations